A review of botany, phytochemistry, and pharmacology of the mangrove apple Sonneratia alba J. Sm. - Charuu P. Kulkarnii, Sonal M. Manohar (Journal of Applied Pharmaceutical Science, 2024)
Mangroves are salt-tolerant plants that form distinctive communities and ecosystems. To survive in a harsh environment, mangroves are believed to produce numerous phytochemicals. Sonneratia alba J. E. Smith is a true type of mangrove plant belonging to the family Lythraceae. This evergreen tree has been widely distributed in the Indo-West Pacific region and is a common species along both the east and west coasts of India. It is the maiden mangrove species in India that has received recognition as the state mangrove plant by the state of Maharashtra. This mangrove has been widely used in traditional medicine for treating skin disorders, bleeding injuries, diarrhoea, and so on. Its bioactivity can be attributed to its phytochemical content, which is rich in phenolics, steroids, tannins, terpenoids, and so on. This review is an attempt to compile various phytochemical and bioactivity investigations done on S. alba. Results indeed showcase its therapeutic prospects as indicated by the wide range of secondary metabolites and biological activities.
Keywords: Antimicrobial, ethnomedicine, pharmacognosy, S. alba, pedada, perepat